Relationships between visceral/subcutaneous adipose tissue FABP4 expression and coronary atherosclerosis in patients with metabolic syndrome - Gormez, Selcuk; Erdim, Refik; Akan, Gokce; Caynak, Baris; Duran, Cihan; Gunay, Demet; Sozer, Volkan; Atalar, Fatmahan (ELSEVIER SCIENCE INC, 2020)
Background: Cytoplasmic fatty acid-binding proteins facilitate the transport of lipids to specific compartments in cells. Fatty acid-binding protein 4 (FABP4), also known as aP2 or A-FABP, plays a key role in the development of atherosclerosis, insulin resistance, obesity, and metabolic syndrome (MS). The FABP4 polymorphisms are associated with protein expression changes in vitro and metabolic and vascular alterations in vivo. The aim of this study was to investigate the association between FABP4 messenger ribonucleic acid (mRNA) expression levels in epicardial (EAT), pericardial (PAT), and subcutaneous adipose tissues (SAT), and the extent of coronary atherosclerosis in coronary artery disease (CAD) patients with MS. Furthermore, the relationship between the extent of coronary atherosclerosis and epicardial adipose tissue volume (EATV) and FABP4 gene variations was evaluated. Patients and methods: A total of 37 patients undergoing coronary artery bypass grafting because of CAD (MS CAD group) and 23 non-MS patients undergoing heart valve surgery (control group) were included. Coronary angiography was performed for all patients and the extent of coronary atherosclerosis was assessed using the Sullivan's scoring system. The mRNA expression levels of FABP4 gene in EAT, PAT, and SAT, and FABP4 polymorphisms were analyzed using the quantitative real-time polymerase chain reaction (qRT-PCR). Results: An increased FABP4 expression was observed in EAT and PAT of MS CAD group compared to controls. In the MS CAD group, FABP4 mRNA expression levels in EAT was 2.8-fold higher compared to PAT. The expression of FABP4 in EAT was positively correlated with the extent of atherosclerosis and EATV in MS CAD group (r = 0.588, P = 0.001, r = 0.174, P = 0.001, respectively). There were no correlations between PAT and SAT versus the extent of atherosclerosis and EATV. The FABP4 EAT mRNA expression levels were found to significantly increase in mutant allele carriers of rs1054135, whereas they significantly decreased in mutant allele carriers of rs77878271 (T-87C) in MS CAD group (P < 0.05). The extent of atherosclerosis was also found to be significantly associated with rs1054135 (P < 0.05). A cut-off point of 57.5 cm(3) EATV was used indicating the presence of CAD with a significant area under the curve of 0.783%, 98% sensitivity, and 100% specificity (95% CI 0.620-0.880; P < 0.05). Conclusions: Our study results suggest that FABP4 expression in EAT is strongly associated with the extent of atherosclerosis and EATV in MS CAD patients. (C) 2019 Published by Elsevier Inc.
Keywords: Coronary atherosclerosis; Fatty acid-binding protein 4; Epicardial adipose tissue; Epicardial adipose tissue volume; Metabolic syndrome; Single nucleotide polymorphism; ACID-BINDING PROTEIN; EPICARDIAL FAT VOLUME; INSULIN-RESISTANCE; LIPID-METABOLISM; ARTERY-DISEASE; RISK; AP2; CALCIFICATION; ASSOCIATION; ADIPOKINES; Cardiovascular System & Cardiology; Pathology